Assessment of Radiation Dose to Patients during Single Photon Emission Computed Tomography (Spect) 99mtc-Sestamibi Myocardial Perfusion Imaging (Mpi) In Niamey- Niger - Idrissa, A.S. (University of Ghana, 2016)
Radiation absorbed dose for patients undergoing myocardial perfusion has been calculated for technetium-99m Hexakis-2-methoxy-2-methylpropyl-isonitrile (99mTc-Sestamibi) at the Nuclear Medicine Department of Abdou Moumouni University. Thirty patients were scanned and image quantification was achieved using MedisoInterViewXP® software. An activity of370 MBq (10 mCi) of 99mTc-Sestamibi was administered for stress and 1110 MBq (30 mCi) for rest. A 256 x 1024 matrix size and a speed of 250 mm per minute were used to acquire the whole body image at 10 minutes, 2 hours and 4 hours after injection of 99mTc-Sestamibi for heart, liver and kidneys quantifications and 10 minutes, 20 minutes and 2 hours for urinary bladder quantification. The activities of the heart, liver, kidneys and urinary bladder were determined using the conjugate view method. The uptake of 99mTc-Sestamibi in the heart, liver and kidneys were respectively 2.17%, 6.53% and 5%, 10 minutes after injection and were in good agreement with the work of Wacker’s et al of respectively 1.5±0.4%, 5.9±2.9% and 10.6±2.2% 5 minutes after injection. The cumulative activities for the heart, liver, kidneys and urinary bladder were respectively30.81MBq/h, 74.98MBq/h, 39.09MBq/h, 136.25MBq/h for the stress and 86.78MBq/h, 244.77MBq/h, 108.76MBq/h and 338.80MBq/h for the rest. The difference in the absorbed dose values obtained was less than 10% except for kidneys which was about 15% for both female and male patients. Both methods found a relatively high absorbed dose per unit of injected activity (mGy/MBq) for urinary bladder and ovaries as target-organs for female patients. Also the uncertainties were in the good agreement according to Stabin.
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Radiation Dose; Single Photon Emission Computed Tomography; Myocardial Perfusion Imaging; Niamey- Niger